2021
DOI: 10.1177/09612033211061850
|View full text |Cite
|
Sign up to set email alerts
|

Comparing pregnancy outcomes in patients with criteria and non-criteria autoimmune disease: A systematic review

Abstract: Background Not all patients fulfil criteria for specific autoimmune rheumatic diseases (ARDs) and are then defined as having non-criteria (nc)ARD. It is uncertain whether well-recognised associations with adverse pregnancy outcomes in patients with criteria ARD also exist in patients with ncARD or undifferentiated connective tissue disease (UCTD). Therefore, we undertook a systematic review of the prevalence of adverse pregnancy outcomes in various ncARD and UCTD compared with criteria ARD to identify whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(237 reference statements)
0
2
0
Order By: Relevance
“…NC‐OPAS can increase the risk of adverse pregnancy outcomes, and a systematic review found that patients in NC‐OAPS and OAPS had a similar risk of developing pregnancy complications 37 . The administration characteristics and pregnancy outcomes are described in detail in Tables 5 and 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NC‐OPAS can increase the risk of adverse pregnancy outcomes, and a systematic review found that patients in NC‐OAPS and OAPS had a similar risk of developing pregnancy complications 37 . The administration characteristics and pregnancy outcomes are described in detail in Tables 5 and 6.…”
Section: Discussionmentioning
confidence: 99%
“…NC-OPAS can increase the risk of adverse pregnancy outcomes, and a systematic review found that patients in NC-OAPS and OAPS had a similar risk of developing pregnancy complications. 37 The administration characteristics and pregnancy outcomes are described in detail in Tables 5 and 6. Patients with standard anticoagulation therapy can have pregnancy outcomes, and the live birth rate was higher in the NC-OAPS than in the OAPS group (74.17% vs. 68.09%, p = .002), which are close to data from other centers 13 We found a significantly higher live birth rate in the NC-OAPS group, a similar outcome was found in the UROAPS registry, with 85% in the OAPS group and 89.6% in the NC-OAPS group.…”
Section: Discussionmentioning
confidence: 99%